Empirical Test of Composite Stock Price Index: Regional Stock Index - Wulandari, Rosita; Pratiwi, Adhitya Putri; Nopagia, Nopagia; Suripto, Suripto (Universitas Pamulang, 2023)
The Composite Stock Price Index (JCI) is an indicator of price movements of all shares on the Indonesia Stock Exchange where one of the factors that can influence the movement of the JCI in Indonesia is the Global Stock Index. This study aims to determine the effect of the Global Stock Index on the Composite Stock Price Index (CSPI) on the Indonesia Stock Exchange, and to analyze the Global Stock Index which has a dominant influence on the JCI. The object of this research was conducted on 5 global stock indices that are located close to and which have a major influence on the world economy on the JCI on the Indonesia Stock Exchange, which consist of the American index with the Dow Jones (DJIA), the Japanese index with the Nikkei 225 (N225), Singapore with the index Strait Times Index (STI), Malaysia with the Kuala Lumpur Composite Index (KLCI) and Hong Kong. with the Hang Seng Index (HSI). The data used is secondary data in the form of monthly. The analytical method used in this study is Ordinary Least Square (OLS) with Eviews version 9 program analysis. The results of the study show that DJIA, Nikkei225, STI, and HIS partially have no effect on the Indonesian Stock Exchange Composite Stock Price Index, while KLCI has an effect on the Indonesia Stock Exchange Composite Stock Price Index.